Geoelectric studies of the Belgorod-Sumy megablock of the northern slope of the Dnieper-Donets Trough - Shirkov, B.; Perestyuk, O.; Kushnir, A. (Geofizicheskiy Zhurnal, 2015)
Processing of long-term Earth’s electromagnetic field observations was performed using two software systems (PRC_MTMV and PTS), frequency distribution of the amplitude and phase of impedance, apparent resistivity, horizontal components of the magnetic tensor and tipper were obtained. Minimum on the descending part of ρk curves according to the results of a qualitative assessment corresponds to the conductor at a depth of 50—150 km.